Effect of oral hygiene instructions in the maintenance of periodontal health - Koppuravuri Venkata Tirumala Susmitha; Jahnavi Manukonda; Tara Kondapaneni; Manaswini Muppaneni; Anumala Deepa; Ravindranath Dhulipalla (SRM Journal of Research in Dental Sciences)
Background: Empowering individuals with knowledge and skills is necessary for maintaining good oral hygiene. Supplementing chairside oral hygiene instructions can enhance patient education in maintaining proper oral hygiene. Audiovisual aids offer a dynamic and visual medium for demonstrating proper techniques, showcasing the consequences of poor oral hygiene, and highlighting the benefits of preventive measures. Aim: This study aims to evaluate the influence of oral hygiene instructions on sustaining periodontal health in patients. Materials and Methods: Forty-two patients were divided into two groups containing 21 participants. Baseline measurements were taken for the Simplified Oral Hygiene Index (OHI-S) and the Patient Hygiene Performance (PHP) Index. After these initial recordings, scaling was performed, followed by the delivery of oral hygiene instructions. Group I received instructions via videos, while Group II received verbal instructions. The patients were recalled 15 days postscaling for a follow-up, during which OHI-S and PHP Index were re-recorded. Results: The data analysis was conducted using paired t-tests and unpaired t-tests. The mean value of the OHI-S and PHP Index after giving instructions via videos is more beneficial than orally. Group I showed a statistically significant difference compared to Group II. Conclusion: The study concluded that oral hygiene instructions delivered through audiovisual aids have a positive effect on the periodontal health of patients. There is a potential benefit in enhancing instruction methods using audiovisual aids to achieve better reinforcement.